2018
DOI: 10.1016/j.celrep.2018.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Ablation in Adipocytes Induces Insulin Resistance and Reveals Roles for Lipid Peroxide and Nrf2 Signaling in Adipose-Liver Crosstalk

Abstract: SUMMARY Autophagy is a homeostatic cellular process involved in the degradation of long-lived or damaged cellular components. The role of autophagy in adipogenesis is well recognized, but its role in mature adipocyte function is largely unknown. We show that the autophagy proteins Atg3 and Atg16L1 are required for proper mitochondrial function in mature adipocytes. In contrast to previous studies, we found that post-developmental ablation of autophagy causes peripheral insulin resistance independently of diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 35 publications
4
82
1
Order By: Relevance
“…This is due to mitophagy (a type of autophagy where the mitochondria is degraded), which is highly activated during maturation of adipocytes and electron microscope results from an early morphological study show active involvement of autophagosomes in removal of mitochondria 34 . Even though mitophagy reduces mitochondrial count during adipose maturation, it is also involved in maintaining appropriate mitochondrial function in mature adipocytes 35 . Although autophagy is crucial for proper functioning and differentiation of adipocytes 9,36,37 , defective regulation during obesity causes metabolic abnormalities, leading to MetS [38][39][40] .…”
Section: Autophagy In Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to mitophagy (a type of autophagy where the mitochondria is degraded), which is highly activated during maturation of adipocytes and electron microscope results from an early morphological study show active involvement of autophagosomes in removal of mitochondria 34 . Even though mitophagy reduces mitochondrial count during adipose maturation, it is also involved in maintaining appropriate mitochondrial function in mature adipocytes 35 . Although autophagy is crucial for proper functioning and differentiation of adipocytes 9,36,37 , defective regulation during obesity causes metabolic abnormalities, leading to MetS [38][39][40] .…”
Section: Autophagy In Obesitymentioning
confidence: 99%
“…However, when autophagic genes Atg3 and Atg16L1 were deleted in mature adipocytes, these knockout mice exhibited insulin resistance compared to control mice. Atg3 and Atg16L1 knockout mice showed impairments in glucose tolerance and insulin sensitivity with increased serum insulin levels indicating development of peripheral insulin resistance 35 . In addition, Atg3 and Atg16L1 knockout mice exhibited dysfunctional mitochondria and increased accumulation of lipid peroxides in adipose tissue depots indicating potential long-term threats of deletion of autophagy in mature adipocytes 35 .…”
Section: Autophagy and Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they demonstrated that the adipocyte-specific Atg7 knockout mouse had a lean phenotype with decreased white adipose mass and enhanced insulin sensitivity. However, more recently, Cai et al showed a protective effect of autophagy in mature adipocyte function [90]. They showed that autophagy proteins are required for adequate mitochondrial function and that the post-development ablation of autophagy caused insulin resistance.…”
Section: Adipose Tissuementioning
confidence: 99%
“…Thus, the global overexpression of Atg5 activates autophagy and also promotes a lower adipose tissue mass in both subcutaneous and visceral deposits, as well as an increased sensitivity to insulin [38]. In addition, the ablation of Atg3 or Atg16L1 in mature adipocytes promotes insulin resistance in the absence of changes in body weight or in the percentage of fat mass [39]. Atg3 ablated mice display an increase in the crown-like adipocytes present in vWAT, thereby suggesting the implication of inflammation in the development of insulin resistance [39].…”
Section: Impact Of Genetic Cancellation Of Autophagy On Adipose Tissumentioning
confidence: 99%